Quadriceps Activation After Anterior Cruciate Ligament Reconstruction: The Early Bird Gets the Worm! - Ayrton MOIROUX-; Florian FORELLI; Jean MAZEAS; Alexandre JM RAMBAUD; Andreas BJERREGAARD; Jérôme RIERA (North American Sports Medicine Institute, 2024)
Arthrogenic Muscle Inhibition (AMI) is a phenomenon observed in individuals with joint injury or pathology, characterized by a reflexive inhibition of surrounding musculature, altered neuromuscular control, and compromised functional performance. After anterior cruciate ligament reconstruction (ACLR) one of the most obvious consequences of AMI is the lack of quadriceps activation and strength. Understanding the underlying mechanisms of AMI is crucial for developing effective therapeutic interventions. The surgical procedure needed to reconstruct the ACL has biochemical et physiological consequences such as inflammation, pain, and altered proprioception. These alterations contribute to the development of AMI. Therapeutic interventions aimed at addressing AMI encompass a multidimensional approach targeting pain reduction, inflammation management, proprioceptive training, and quadriceps activation. Early management focusing on pain modulation through modalities like ice, compression, and pharmacological agents help mitigate the inflammatory response and alleviate pain, thereby reducing the reflexive inhibition of quadriceps. Quadriceps activation techniques such as neuromuscular electrical stimulation (NMES) and biofeedback training aid in overcoming muscle inhibition and restoring muscle strength. NMES elicits muscle contractions through electrical stimulation, bypassing the inhibitory mechanisms associated with AMI, thus facilitating muscle activation and strength gains. Comprehensive rehabilitation programs tailored to individual needs and stage of recovery are essential for optimizing outcomes in AMI. The objective of this clinical viewpoint is to delineate the significance of adopting a multimodal approach for the effective management of AMI, emphasizing the integration of pain modulation, proprioceptive training, muscle activation techniques, and manual therapy interventions. Highlighting the critical role of early intervention and targeted rehabilitation programs, this article aims to underscore their importance in restoring optimal function and mitigating long-term complications associated with AMI.